FUNGSI FILSAFAT, AGAMA, IDEOLOGI DAN HUKUM DALAM PERKEMBANGAN POLITIK DI INDONESIA - Peni Jati Setyowati (Universitas Airlangga, 2016)
In democratic system in Indonesia, the growth of political parties shows that the democratic system has developed. The development of the democratic system has the objective to incernate the ideals of Indonesia as set forth in paragraph 4 of the Preamble of the Indonesian Constitution 1945. The political role in the development of national law in Indonesia cannot be separated from the context of history, religion, and ideology. The development of political shows the diversity of views. The views between the political parties in determining the political direction is based on the ideas and ideologies that have grown in it. The process of legal formation in the birth of positive law (in abstracto) is always influenced by certain political configurations that interact in the process. The ideas in this ideology would also have been based on the theory of truth which has been adopted from each party. Differences in the ideological views of political parties also gives effect to the development of legislation character and policy direction of the Government in determining the laws that determine the development of the legal system in Indonesia.